Cortical Activation Patterns of Different Masking Noises and Correlation With Their Masking Efficacy, Determined by Functional Near-Infrared Spectroscopy - Sun, Qiyang; Wang, Xianren; Huang, Bixue; Sun, JinCangjian; Li, Jiahui; Zhuang, Huiwen; Xiong, Guanxia (Frontiers in Human Neuroscience, 2020)
Acoustic therapy in tinnitus treatment is poorly characterized, and efficacy assessment depends on subjective descriptions. Narrow-band noise, notched sound, and white noise have positive therapeutic effects on monotonous tinnitus. Considering the tonotopic characteristics of the auditory system and the spectral characteristics of these three masking sounds, the activation pattern of the auditory cortex and the mechanism of inhibiting tinnitus may be different. The aim of this study was to compare the activation patterns of three spectrally different masking noises, and study the correlation between the masking effects and variational amplitude of HbO（oxygenated hemoglobin）in the corresponding cortical regions. We also assessed near-infrared spectroscopy brain function imaging (NIRS) as an objective assessment tool in acoustic therapy. Patients with tinnitus and volunteers without persistent tinnitus were enrolled in this study. The subjects were seated in a sound-proof room, with two optode arrays covering bilateral temporal lobe. Auditory stimuli were presented; stimulation sequences followed the block design: different noises appeared randomly and repeated in 5 cycles. Finger-tapping and pure-tone stimulation tests were conducted in the control group, while tinnitus match and residual inhibition were performed in the tinnitus group. The data analyses were conducted using the NIRS_SPM toolbox. In the control group, the finger-tapping test showed significant activation in the central anterior gyrus. In the pure tone stimulation test, the 6000 Hz and 500 Hz pure tones did not show a significant activation signal. Twenty cases in the control group and 13 in the tinnitus group showed deactivation and activation patterns in BA21 during narrow band noise and white noise stimulation respectively. Notched sound did not cause significant activation of the auditory cortex in both groups. The depth of residual inhibition induced by the narrow-band noise and white noise significantly correlated with ΔHbO in the region of interest. However, neither depth nor duration of the residual inhibition induced by white noise correlated with the ΔHbO. Thus, NIRS showed three cortical activation patterns induced by three different masking noises, and correlations between residual inhibition effects and change of HbO amplitude were found. NIRS could therefore be applied in objective assessment of acoustic therapy.